Analysis of the Kemata Air Senjoyo Tourism Area Development Strategy for Tourist Interest - Yadina Waruwu; Dyah Palupiningtyas (Pusat Riset dan Inovasi Nasional, 2024)
The ecotourism potential in Senjoyo Village, Salatiga, lies in its beautiful natural landscapes and enjoyable water activities, supported by adequate infrastructure and facilities. Accessibility to Senjoyo Salatiga is convenient, with a friendly local community. The ecotourism management strategy in Senjoyo Salatiga focuses on maximizing promotion, improving road access, enhancing and supplementing ecotourism activity facilities, fostering the local community as ecotourism guides, and implementing training on tourism awareness and the importance of preserving the ecotourism site in Senjoyo Salatiga.